2011
DOI: 10.2215/cjn.01880211
|View full text |Cite
|
Sign up to set email alerts
|

Referral Patterns and Outcomes in Noncritically Ill Patients with Hospital-Acquired Acute Kidney Injury

Abstract: SummaryBackground and objectives Despite modern treatment, the case fatality rate of hospital-acquired acute kidney injury (HA-AKI) is still high. We retrospectively described the prevalence and the outcome of HA-AKI without nephrology referral (nrHA-AKI) and late referred HA-AKI patients to nephrologists (lrHA-AKI) compared with early referral patients (erHA-AKI) with respect to renal function recovery, renal replacement therapy (RRT) requirement, and in-hospital mortality of HA-AKI.Design, setting, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 33 publications
(37 reference statements)
8
66
0
Order By: Relevance
“…Even mild AKI is no longer considered to be benign, but rather an independent predictor of mortality (18,19,25). Surprisingly, our data demonstrated that more severe AKI was not necessarily associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Even mild AKI is no longer considered to be benign, but rather an independent predictor of mortality (18,19,25). Surprisingly, our data demonstrated that more severe AKI was not necessarily associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 51%
“…AKI is an important contributor to CKD. Previous studies have highlighted increased risks of de novo CKD following episodes of AKI with incomplete recovery (3,15,16,22,25). In this study, one third of patients developed de novo CKD or progression of preexisting CKD.…”
Section: Discussionmentioning
confidence: 73%
“…CKD was identified by the diagnosis codes, a baseline eGFR,60 ml/min per 1.73 m 2 in patients with AKI, or the highest eGFR,60 ml/min per 1.73 m 2 in patients without AKI (19). The burden of comorbidity was determined using the Charlson comorbidity score (20).…”
Section: Determination Of Comorbiditymentioning
confidence: 99%
“…Although consistent with data from South Africa (SA), [17] this is in contrast to the distribution of AKI in the developed world which predominantly occurs in elderly male populations. [19][20][21] The data also suggest that AKI associated with intrinsic renal disease/glomerular injury presents predominantly as AKI3. This is also in keeping with our previous data from Ethiopia in which 48% of patients presented with AKI3.…”
Section: Discussionmentioning
confidence: 88%